2021
DOI: 10.1007/s40843-021-1823-9
|View full text |Cite
|
Sign up to set email alerts
|

Photoconverting polyethylene terephthalate into exclusive carbon dioxide by heterostructured NiO/Fe2O3 nanosheets under mild conditions

Abstract: Degradation of polyethylene terephthalate (PET) plastics by the traditional technologies usually requires high energy consumption and encounters poor product selectivity. Herein, we report the photoconversion of PET into carbon dioxide with 100% selectivity by in-plane heterostructured NiO/Fe 2 O 3 nanosheets in pure water under normal temperature and pressure. High-resolution transmission electron microscopy, X-ray absorption near-edge spectroscopy and X-ray photoelectron spectra demonstrate the construction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Summary of plastic conversion routes over photocatalysts. Fe 2 O 3 photocatalyst 88. In this case, the internal electric field between NiO and Fe 2 O 3 contributed to electron transfer from NiO to Fe 2 O 3 , as verified by the shift of Ni 2p in NiO/Fe 2 O 3 to a higher binding energy as compared to pure NiO.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Summary of plastic conversion routes over photocatalysts. Fe 2 O 3 photocatalyst 88. In this case, the internal electric field between NiO and Fe 2 O 3 contributed to electron transfer from NiO to Fe 2 O 3 , as verified by the shift of Ni 2p in NiO/Fe 2 O 3 to a higher binding energy as compared to pure NiO.…”
mentioning
confidence: 64%
“…The new vibration bands, including C≡C and C═O bond stretching, were formed, indicating the dissociation of the carbon chain and oxidation of the polymer, which was confirmed by the carbonyl index measurement where the enhanced carbonyl index manifested the generation of several intermediates from PS degradation (e.g., ketone, aldehyde, and carboxylic acid). Apart from polyolefin degradation, raw PET could be degraded into CO 2 over NiO/Fe 2 O 3 photocatalyst 88 . In this case, the internal electric field between NiO and Fe 2 O 3 contributed to electron transfer from NiO to Fe 2 O 3 , as verified by the shift of Ni 2p in NiO/Fe 2 O 3 to a higher binding energy as compared to pure NiO.…”
Section: Photocatalytic Plastic Conversionmentioning
confidence: 90%
“…Solid evidence from in‐situ characterizations and isotope‐labeling experiments indicated that PET was mineralized into CO 2 through the stepwise oxidation of CH 3 O*, CHO*, and COOH* intermediates (Figure 2e). [17] Although interface engineering has been widely used for the removal of photocatalytic pollutants, only a few studies have focused on the plastic degradation, and more significant work should be conducted.…”
Section: Photocatalytic Conversionmentioning
confidence: 99%
“…Given that the ultrathin layered double hydroxides (LDHs) nanosheets can be readily transformed into mixed metal oxides as 2D building blocks by a straightforward annealing treatment, forming seamless in-plane heterojunctions in virtue of in situ topotactic transformation procedure. [26][27][28] Herein, we put forward a successful synthesis of ultrathin in-plane heterostructured NiO/Cr 2 O 3 nanosheets by using ultrathin NiCr-LDH nanosheets as applicatory precursors. Meanwhile, taking such hybrid system as a prototype, we highlight the significant efficacy of in-plane heterostructure on tailoring the d-band centers of Nibased catalysts for high-efficiency MOR.…”
Section: Introductionmentioning
confidence: 99%